2018
DOI: 10.5194/hess-22-1157-2018
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective forecasts of the upcoming winter season snow accumulation in the Inn headwaters (European Alps)

Abstract: Abstract. This article presents analyses of retrospective seasonal forecasts of snow accumulation. Re-forecasts with 4 months' lead time from two coupled atmosphere-ocean general circulation models (NCEP CFSv2 and MetOffice GloSea5) drive the Alpine Water balance and Runoff Estimation model (AWARE) in order to predict mid-winter snow accumulation in the Inn headwaters. As snowpack is hydrological storage that evolves during the winter season, it is strongly dependent on precipitation totals of the previous mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Previously, both dynamical and statistical models have been used to predict, for example, precipitation over the British Isles (Baker et al 2018a;Ossó et al 2018), precipitation in Europe (Dunstone et al 2018;Totz et al 2017), the wintertime NAO index (Dobrynin et al 2018;Hall et al 2017;Scaife et al 2014;Stockdale et al 2015), snow accumulation over the Alps (Förster et al 2018), sea ice cover in the Baltic Sea (Karpechko et al 2015), wintertime European temperatures (Folland et al 2012), and monthly temperatures at various midlatitude locations (Karpechko 2015).…”
Section: Several Potential Sources Of Predictability Have Beenmentioning
confidence: 99%
“…Previously, both dynamical and statistical models have been used to predict, for example, precipitation over the British Isles (Baker et al 2018a;Ossó et al 2018), precipitation in Europe (Dunstone et al 2018;Totz et al 2017), the wintertime NAO index (Dobrynin et al 2018;Hall et al 2017;Scaife et al 2014;Stockdale et al 2015), snow accumulation over the Alps (Förster et al 2018), sea ice cover in the Baltic Sea (Karpechko et al 2015), wintertime European temperatures (Folland et al 2012), and monthly temperatures at various midlatitude locations (Karpechko 2015).…”
Section: Several Potential Sources Of Predictability Have Beenmentioning
confidence: 99%
“…The ESP method was originally developed in the snow-dominated catchments of the western United States (e.g., Franz et al, 2003), but has shown skill in other regions, including the UK (Harrigan et al, 2018), European Alps (Förster et al, 2018), Sweden (Girons Lopez et al, 2020), New Zealand (Singh, 2016), Australia (Pagano et al, 2010;Wang et al, 2011), and China (Yuan et al, 2016). Simplicity and efficiency make ESP a popular choice for operational forecasting.…”
mentioning
confidence: 99%
“…The choice of the appropriate complexity depends on the objective of the work. Förster et al (2018) aims at forecasting February SWE anomalies spatially-averaged at the catchment scale, so they employed a simple hydrological snow model driven by air temperature and precipitation anomalies only, at coarse (monthly) time resolution. An advantage of this simple approach is the limited input data requirement and the low computational load of the simulations, at the expense of higher uncertainty in the output results.…”
Section: Impact Of the Choice Of The Snow Modelmentioning
confidence: 99%
“…This approach allows to reduce the uncertainty associated the reference data compared to more common cases in which reference data are simulated by hydrological models and model errors affect the quality of the reference data (i.e. Förster et al, 2018).…”
Section: Uncertainty In the Validation Datamentioning
confidence: 99%
See 1 more Smart Citation